Collected writings of John Maynard Keynes Vol XVII - Activities 1920-1922 Treaty revision and reconstruction - Keynes, John Maynard; Keynes, John Maynard (Cambridge Cambridge University Press, 2013)
Reactions to the economic consequences of the peace